2013 22nd International Conference on Computer Communication and Networks (ICCCN) 2013
DOI: 10.1109/icccn.2013.6614155
|View full text |Cite
|
Sign up to set email alerts
|

MOTAG: Moving Target Defense against Internet Denial of Service Attacks

Abstract: Abstract-Distributed Denial of Service (DDoS) attacks still pose a significant threat to critical infrastructure and Internet services alike. In this paper, we propose MOTAG, a moving target defense mechanism that secures service access for authenticated clients against flooding DDoS attacks. MOTAG employs a group of dynamic packet indirection proxies to relay data traffic between legitimate clients and the protected servers. Our design can effectively inhibit external attackers' attempts to directly bombard t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 20 publications
1
63
0
Order By: Relevance
“…• What to move: 'What to move' refers to what system configuration attribute (i.e., attack surface) can be dynamically changed to confuse attackers. The example system or network attributes that can be changed include instruction sets [86,123], address space layouts [135], IP addresses [3,10,79,88,138], port numbers [97], proxies [83], virtual machines [165,20], operating systems [148], or software programs [76]. Table III summarizes the moving elements by MTD techniques in different system layers [4,69].…”
Section: B Key Design Principlesmentioning
confidence: 99%
“…• What to move: 'What to move' refers to what system configuration attribute (i.e., attack surface) can be dynamically changed to confuse attackers. The example system or network attributes that can be changed include instruction sets [86,123], address space layouts [135], IP addresses [3,10,79,88,138], port numbers [97], proxies [83], virtual machines [165,20], operating systems [148], or software programs [76]. Table III summarizes the moving elements by MTD techniques in different system layers [4,69].…”
Section: B Key Design Principlesmentioning
confidence: 99%
“…Figure 2 shows the HARM of the virtualized system. The AT shown in Figure 2 for V M 1 (as shown in Table 1 [14], [15], [16] Application [17], [18] Diversity Topology [19], [20] Application [21], [22], [23], [24], [25], [26] Redundancy Topology [27], [28] Application [29], [30], [31], [32] …”
Section: Generating a Harmmentioning
confidence: 99%
“…At the application layer, Vikram et al [17] randomized HTML elements to mitigate web bots. Jia et al [18] showed the secure service access for clients by relocating secret proxies and shuffling client-to-proxy assignments.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, besides keeping up with novel and advanced techniques for identifying and patching system vulnerabilities, detecting malware, and building new systems with security embedded from scratch, exploits, e.g., address space randomization (ASLR) [2][3][4] and instruction set randomization (ISR) [5,6]. Higher level MTD approaches have been mainly based on diversity-inspired software assignment [7][8][9], system and network re-configuration, substitution, and shuffling techniques [10][11][12][13]. In military environments, frequency hopping techniques such as Frequency Hopping Spread Spectrum (FHSS) [14] has been used to defend against eavesdropping and radio jamming for long time.…”
Section: Introductionmentioning
confidence: 99%